2021
DOI: 10.1145/3485628
|View full text |Cite
|
Sign up to set email alerts
|

Mip* = Re

Abstract: Note from the Research Highlights Co-Chairs: A Research Highlights paper appearing in Communications is usually peer-reviewed prior to publication. The following paper is unusual in that it is still under review. However, the result has generated enormous excitement in the research community, and came strongly nominated by SIGACT, a nomination seconded by external reviewers. The complexity class NP characterizes the collection of comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
79
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 15 publications
0
79
0
Order By: Relevance
“…Our results can be generalized to general convex resource theories [30] and the operator theory. Quantum entanglement was shown being at the centre of a new mathematical proof recently [31]. We expected that our findings will stimulate further investigation on the quantum theory and practical applications in other fields.…”
mentioning
confidence: 69%
“…Our results can be generalized to general convex resource theories [30] and the operator theory. Quantum entanglement was shown being at the centre of a new mathematical proof recently [31]. We expected that our findings will stimulate further investigation on the quantum theory and practical applications in other fields.…”
mentioning
confidence: 69%
“…The reference[6] actually only deals with strongly self-absoring C * -algebras, but the proof there implies the result that we mention above 7. By the work in[7, Remark 5.8], the failure of CEP already implies that E, should it exist, could not be isomorphic to E ⊗ E 8. In general, the prime model of a theory is a model which elementarily embeds into any other model of the theory and, if it exists, it is automatically unique.…”
mentioning
confidence: 85%
“…In the embeddable situation, R is a finitely generic embeddable factor (see [7,Corollary 3.14]), whence the finite forcing companion is simply the complete theory of R. Since R embeds in any model of its theory (due to the axiomatizability of being McDuff), the fact that R has the generalized Jung property implies that it is the prime model of its theory. 8 It is currently unknown whether or not T f has a prime model. However, if it does, then it is a non-embeddable factor with the Jung property: Theorem 3.…”
Section: Theorem 2 If the Enforceable Factor Exists Then It Has The J...mentioning
confidence: 99%
See 1 more Smart Citation
“…In [18] it was shown that for every d ≥ 11, there are UCPT maps with an exact factorization through M d (C) ⊗ N , where N a von Neumann algebra of type II 1 which cannot be replaced by any finite dimensional von Neumann algebra. In view of [6,Theorem 3.7] and the announcement in [12] that the Connes Embedding Problem has a negative answer, there are factorizable maps, for some (presumably very large) d, which cannot even be approximated by maps with exact factorizations through matrix algebras.…”
Section: Introductionmentioning
confidence: 99%